Genomic determinants of entomopathogenic fungi and their involvement in pathogenesis - Vidhate, Ravindra P.; Dawkar, Vishal V.; Punekar, Sachin A.; Giri, Ashok P. (Microbial Ecology, 2023)
Entomopathogenic fungi offer an effective and eco-friendly alternative to curb insect populations in biocontrol strategy. The evolutionary history of selected entomopathogenic fungi indicates their ancestral relationship with plant endophytes. During this host shifting, entomopathogenic fungi must have acquired multiple mechanisms, including a combination of various biomolecules that make them distinguishable from other fungi. In this review, we focus on understanding various biochemical and molecular mechanisms involved in entomopathogenesis. In particular, we attempt to explain the indispensable role of enlarged gene families of various virulent factors, viz. chitinases, proteases, lipases, specialized metabolites, and cytochrome P450, in entomopathogenesis. Our analysis suggests that entomopathogenic fungi recruit a different set of gene products during the progression of pathogenesis. Knowledge of these bio-molecular interactions between fungi and insect hosts will allow researchers to execute pointed efforts towards the development of improved entomopathogenic fungal strains.
Keywords: Biocontrol; Chitinases; Endophytic fungi; Entomopathogenic fungi; Hydrolytic enzymes; Insect pests